Odpowiedzi

2009-10-29T19:45:31+01:00
6x+y=8
-6x+4y-2=0

5y-2=8
5y=10
y=5


x+y=5
-x+2y=4

3y=9
y=3


x+½y=4
2x-y=4

x=½y=4
x-½y=2

2x=6
x=3

2009-10-29T19:48:29+01:00
6x+y=8
-6x+4y-2=0

6x+y=8
-6x+4y=2
_________
+
5y=10|:5
y=2
6x=6|:6
x=1


x+½y=4|*(-2)
2x-y=4

-2x-2y=-8
2x-y=4
_________
+
-3y=-4|:<-3>
y+0.75
2x-y=4
2x-0.75=4
2x=4.75|:2
x=2.375



x+y=5
-x+2y=4
_________
+
3y=9|:3
y=3
x+3=5
x=2
Najlepsza Odpowiedź!
2009-10-29T19:55:49+01:00
A)
6x+y =8
-6x+y =2

6x+y-6x+y = 8+2
2y =10
y =5

6x+5 = 8
6x =3
x =3/6 = 1/2

b)
x+1/2y =4 /*2
2x-y =4

2x+y =8
2x-y =4

2x+y+2x-y =8+4
4x =12
x=3

3+1/2y =4
1/2y =1
y =2

c)
x+y =5
-x+y =4
x+y-x+2y =5+4
3y =9
y =3

x+3 =5
x =2